PERSONAL ACCOUNT AS AN ELEMENT OF INFORMATION SYSTEM OF STATISTICS EDUCATION - N. B. Golovanova; A. V. Soroko (Российский технологический журнал)
The article is devoted to the application of information technology in the organization of modern statistics education. The main trends of modernization of statistical instruments due to the changes in the Russian education system are described. The importance of statistics information system creation and its role in the formation of information resources for state management in the field of education are evaluated. The functions of the Ministry of education and science of the Russian Federation as a subject of official statistical registration are shown. Directions of the development of the organizational and technological component of the information system for statistics education are described. This is directly related to the implementation of more advanced technical means for gathering, processing and transfer of data, increase of the automation level for solving statistical tasks, in particular, the introduction of information system elements such as personal account. The appropriateness of the hierarchical approach in the construction of the statistical information system of education is proven. The conceptual basis for the creation of personal accounts is characterized. It is based on the hierarchical structure of the Russian education system and fully provides the solution of the problem of transfer to item-by-item statistics. The author defines the functions of private accounts with consideration for the status of each participant of the information system and presents brief characteristics of technologies for gathering statistical information using the personal account.